Precautionary Savings of Agents with Heterogeneous Risk Aversion - Michele Limosani; Emanuele Millemaci (Economics and Econometrics Research Institute (EERI), 2012)
This paper focuses on the estimation of the importance of the precautionary motive in the wealth accumulation decision. We use a micro dataset containing information on wealth, a subjective measure of income uncertainty and subjective indicators of risk aversion. The latter makes us possible to account for the fact that more risk averse individuals may select themselves into less risky occupations and, therefore, bias results. Restricting our analysis on male employees heads of households living with partner and children, we find that only a small share of wealth is accumulated for the precautionary motive. Our findings suggest that the more risk averse individuals are those who hold less savings. When heterogeneous risk aversion is not taken into account, estimates do not seem to change significantly.
Keywords: D10; D91; D84; 330; Intertemporal choice; Subjective expectations; Precautionary savings; Precautionary wealth; Risk aversion